Exercise May Promote Skeletal Muscle Hypertrophy via Enhancing Leucine-Sensing: Preliminary Evidence - Zhao, Yan; Cholewa, Jason; Shang, Huayu; Yang, Yueqin; Ding, Xiaomin; Liu, Shaosheng; Xia, Zhi; Zanchi, Nelo Eidy; Wang, Qianjin (Frontiers in Physiology, 2021)
Several studies have indicated a positive effect of exercise (especially resistance exercise) on the mTOR signaling that control muscle protein synthesis and muscle remodeling. However, the relationship between exercise, mTOR activation and leucine-sensing requires further clarification. Two month old Sprague-Dawley rats were subjected to aerobic exercise (treadmill running at 20m/min, 6° incline for 60 min) and resistance exercise (incremental ladder climbing) for 4 weeks. The gastrocnemius muscles were removed for determination of muscle fibres diameter, cross-sectional area (CSA), protein concentration and proteins involved in muscle leucine-sensing and protein synthesis. The results show that 4 weeks of resistance exercise increased the diameter and CSA of gastrocnemius muscle fibres, protein concentration, the phosphorylation of mTOR (S2448), 4E-BP1(Thr37/46), p70S6K (Thr389), and the expression of LeuRS, while aerobic exercise just led to a significant increase of protein concentration and the phosphorylation of 4E-BP1(Thr37/46). Moreover, no difference was found for Sestrin2 expression between groups. The current study shows resistance exercise but not aerobic exercise, may increase muscle protein synthesis and protein deposition, and induced muscle hypertrophy through LeuRS/mTOR signaling pathway. However, further studies are still warranted to clarify the exact effects of longer duration of aerobic exercise training.